Front-side nutritional information affects the perception of consumption of UHT milk drinks - Oliveira, Handressa Dark Soares de; Faria, Paula Sperotto Alberto Faria; Gomes, Diego Micheli Sousa; Okwara, Franklin Chidi; Sousa, Hemillio Borges de; Santos, Lorrane Soares do; Cappato, Leandro Pereira; Gadêlha, Stefany Cristiny Ferreira da Silva; Silva, Marco Antônio Pereira da (Food Science and Technology, 2025)
Research indicates that front labeling of foods that mention dietary concerns, such as reduced sugar content, has reduced consumer expectations and their preference for the product. The objective was to analyze the impacts of the new labeling on chocolate-flavored ultra-high temperature dairy products intended for lactose-restricted diets, in accordance with Normative Instruction No. 75 of 2020 and Collegiate Board Resolution No. 429 of 2020. Five dairy products were evaluated through qualitative and quantitative analyses, following the criteria defined by current standards. Additionally, 100 consumers who practice physical activity responded to a questionnaire, analyzing factors such as clarity, accessibility, and the impact of the information contained on labels. The findings indicated that, although most labels met the fundamental requirements, non-conformities were still identified, particularly linked to legibility and the lack of essential information. However, there was a need for greater consumer awareness and supervision to ensure full compliance with the new rules.